1,1′-Diphenyl-3,3′-(p-phenylenedicarbonyl)dithiourea - Wong W. Hung; Ibrahim N. Hassan; Bohari M. Yamin; Mohammad B. Kassim (Acta Crystallographica Section E, 2010)
The molecule of the title compound, C22H18N4O2S2, lies across a crystallographic inversion centre. The central benzene ring forms dihedral angles of 29.39 (9) and 79.11 (12)°, respectively, with the thiourea unit and the terminal phenyl ring. Intramolecular N—H...O hydrogen bonds generate two S(6) ring motifs. In the crystal, molecules are linked into chains along [1overline{1}0] by intermolecular N—H...S hydrogen bonds.